1999
DOI: 10.1111/j.1572-0241.1999.01131.x
|View full text |Cite
|
Sign up to set email alerts
|

How Important Is The Route of Reconstruction After Esophagectomy: A Prospective Randomized Study

Abstract: The posterior mediastinal route of reconstruction is recommended but curative resection (R0) is mandatory to avoid possible complications due to local tumor relapse. After incomplete resection (R1 or R2) we recommend retrosternal reconstruction for better palliation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 22 publications
4
37
0
2
Order By: Relevance
“…In the literature, a pyloric drainage procedure is known to have an unclear effect on reflux [3-5,9,10]. In the present study, the degree of DGR had the definitive tendency to be higher in a gastric tube with a larger pyloric opening.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In the literature, a pyloric drainage procedure is known to have an unclear effect on reflux [3-5,9,10]. In the present study, the degree of DGR had the definitive tendency to be higher in a gastric tube with a larger pyloric opening.…”
Section: Discussionsupporting
confidence: 48%
“…Controversy still exists about the omission of a pyloric drainage procedure and the use of an extra-anatomical route because the evidence from the literature is conflicting [4,5,9-12]. A reason for these conflicting results is that the clinical data from human subjects is not easily reproducible due to many other factors that affect DGR and cannot be completely controlled in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Imada et al 29 observed equivalent absorption in both treatment arms in their study, although emptying may be slower when the conduit is positioned retrosternally. 30…”
Section: Discussionmentioning
confidence: 99%
“…Extra-anato mical esophageal reconstruction offers the advantage that a recurrent intrath oracic tu mor mass will not invade the neo-esophagus [2] [3]. In addition, an extra-anato mical gastric interposition may also be used to bypass a corrosive esophageal injury.…”
Section: Introductionmentioning
confidence: 99%